Assessment as Living Documents of Program Identity and Institutional Goals: A Profile of Missouri University of Science and Technology's Composition Program. - Reardon, Daniel; Wulff, Alexander (Composition Forum)
In this profile we describe changes to the composition program at Missouri University of Science and Technology, prompted by the hiring of the university's first writing program administrator (WPA). We describe our efforts to implement evidence-based best practices in undergraduate writing courses in a context where very little program specific evidence was available. We also describe how challenges of effecting change at a university largely composed of science, technology, engineering, and mathematics (STEM) students has meant that many of the changes have been framed by the spirit of Writing Across the Curriculum (WAC) initiatives. Several new methods of assessment have been introduced to the program, including instructor feedback, student surveys, and skills tests. Allowing assessment to drive standardization has begun a process of measuring the transfer of student knowledge we believe other departments will find interesting. We close by outlining unresolved issues and ongoing challenges as the program moves forward.